BLOG CREATION TRAINING TO INCREASE THE POTENTIAL OF ECO TOURISM THROUGH SOCIAL NETWORK MEDIA - Muhammad Ilham; Agus Iskandar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In an effort to increase the potential of eco tourism through the use of digital technology, this community service program is implemented with the main aim of training eco tourism actors in creating and managing blogs, as well as using social media for tourism promotion. This training is designed to address the lack of digital skills among eco tourism practitioners and improve their skills in creating attractive and effective digital content for online promotions. The method used in this training includes a series of theoretical and practical workshops that focus on the basics of blogging, search engine optimization (SEO), and social media marketing strategies. The results of this training show a significant increase in participants' knowledge and skills in creating blogs and utilizing social media, which is reflected in the increase in the quality of their content and online activities. This study recommends further development of the training curriculum with the integration of advanced techniques and more varied case studies, as well as increased ongoing support for trainees in applying new knowledge and skills in the real context of the ecotourism business.